Genetic Defects and Pro-inflammatory Cytokines in Parkinson's Disease - Magnusen, Albert Frank; Hatton, Shelby Loraine; Rani, Reena; Pandey, Manoj Kumar (Frontiers in Neurology, 2021)
Parkinson's disease (PD) is s a movement disorder attributed to the loss of dopaminergic (DA) neurons mainly in the substantia nigra pars compacta. Motor symptoms include resting tremor, rigidity and bradykinesias, while non-motor symptoms include autonomic dysfunction, anxiety and sleeping problems. Genetic mutation in number of genes, (e.g., LRRK2, GBA, SNCA, PARK2, PARK6, and PARK7) and the resultant abnormal activation of microglial cells are assumed to be the main reason for the loss of DA neurons in PD with genetic causes. Additionally, immune cells infiltration and their participation in major histocompatibility complex I (MHC I) and/or MHCII-mediated processing and presentation of cytosolic or mitochondrial antigens activate the microglial cells and cause the massive generation of the pro-inflammatory cytokines and chemokines, which are all critical for propagation of brain inflammation and the neurodegeneration in PD with genetic and idiopathic causes. Despite of knowing the involvement of several of such immune devices that trigger neuroinflammation and neurodegeneration in PD, the exact disease mechanism or the innovative biomarker that could detect disease severity in PD linked to defects in LRRK2, GBA, SNCA, PARK2, PARK6, and PARK7 genes are largely unknown. The current review has explored the data from genetics, immunology, and the in vivo and ex vivo functional studies that demonstrate that certain genetic defects might contribute to microglial cells activation and massive generation of number of pro inflammatory cytokines and chemokines, which ultimately drive the brain inflammation and lead to the neurodegeneration in PD. Understanding the detail involvement of variety of immune mediators, their source, and the target could provide better understanding of the disease processing. This information might be help in clinical diagnosis, monitoring of disease progression, and early identification of affected individuals.